Differential Expression Analysis of Olfactory Genes Based on a Combination of Sequencing Platforms and Behavioral Investigations in Aphidius gifuensis - Fan, Jia; Zhang, Qian; Xu, Qingxuan; Xue, Wenxin; Han, Zongli; Sun, Jingrui; Chen, Julian (Frontiers in Physiology, 2018)
Aphidius gifuensis Ashmead is a dominant endoparasitoid of aphids, such as Myzus persicae and Sitobion avenae, and plays an important role in controlling aphids in various habitats, including tobacco plants and wheat in China. A. gifuensis has been successfully applied for the biological control of aphids, especially M. persicae, in green houses and fields in China. The corresponding parasites, as well as its mate-searching behaviors, are subjects of considerable interest. Previous A. gifuensis transcriptome studies have relied on short-read next-generation sequencing (NGS), and the vast majority of the resulting isotigs do not represent full-length cDNA. Here, we employed a combination of NGS and single-molecule real-time (SMRT) sequencing of virgin females (VFs), mated females (MFs), virgin males (VMs), and mated males (MMs) to comprehensively study the A. gifuensis transcriptome. Behavioral responses to the aphid alarm pheromone (E-β-farnesene, EBF) as well as to A. gifuensis of the opposite sex were also studied. VMs were found to be attracted by female wasps and MFs were repelled by male wasps, whereas MMs and VFs did not respond to the opposite sex. In addition, VFs, MFs, and MMs were attracted by EBF, while VMs did not respond. According to these results, we performed a personalized differential gene expression analysis of olfactory gene sets (66 odorant receptors, 25 inotropic receptors, 16 odorant-binding proteins, and 12 chemosensory proteins) in virgin and mated A. gifuensis of both sexes, and identified 13 candidate genes whose expression levels were highly consistent with behavioral test results, suggesting potential functions for these genes in pheromone perception.